Effectiveness of Artificial Intelligent Independent Learning (AIIL) with physics chatbot of global warming concept - Alfarizi Ade Karlin Kusuma; Winne Aulia Dyah Maharani; Firmanul Catur Wibowo; Hadi Nasbey; Bayram Costu (Momentum: Physics Education Journal, 2024)
This research aims to analyze the effectiveness of Artificial Intelligent Independent Learning (AIIL) with physics chatbot of global warming concept. Method of research uses the Research & Development method referring to the ADDIE development model. This research was conducted with 64 students at Senior High School in Indonesia who were divided into chatbot-based experimental groups and control groups. The results of this study were obtained by conducting the normalized gain <g> test of 0.60 (medium category) for the control group and 0.87 (high category) in the experimental group. As for the results of the Cohen's D effect-size test, the result was 0.93 with high category AAIL for increasing learning outcome. Thus, the developed AAIL chatbot has high effectiveness in increasing learning outcome.